PERLINDUNGAN HUKUM BAGI KORBAN MENINGGAL DUNIA AKIBAT KECELAKAAN LALU LINTAS DISEBABKAN OLEH JALAN BERLUBANG DITINJAU DARI PERSPEKTIF VIKTIMOLOGI - Agus Rezani (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
Abstract In Article 241 of Law Number 22 The Year 2009 concerning Road Traffic and Transportation, it is stated that every victim of a traffic accident has the right to obtain priority of first aid and care in the nearest hospital in accordance with the provisions of the legislation. Legal protection against victims of traffic accidents is that victims must obtain their rights. Facts that often occur in the field indicate that victims of traffic accidents do not get adequate rights protection. Victims of traffic accidents, both those who died and those who suffered serious or minor injuries were not immediately given information about their rights. Even though the victims of traffic accidents have the right to get compensation from those responsible for traffic accidentsThe method used in this study is a normative juridical method, data or information obtained through library research. From the results of the literature research, secondary data were obtained which included primary legal materials, secondary legal materials, and tertiary legal materials. The problems discussed in this paper are legal rules that can be used to provide legal protection for death victims due to traffic accidents caused by perforated roads, and constraints in providing legal protection for death victims due to traffic accidents caused by hollow roads.Based on the results of the study, it can be concluded that the protection of human rights has been regulated by legislation, in Article 34 paragraph (3) of the 1945 constitution stated that the State is responsible for the provision of adequate health service facilities and public service facilities, this means the State as the holder of power is obliged to provide protection for security and comfort to the people, law number 22 of 2009 concerning road traffic and transportation article 24 (1) road operators who are obliged to immediately and properly repair damaged roads that can cause traffic accidents, continue with paragraph (2) in the event that repairs to damaged roads have not yet been carried out as meant in paragraph (1), operators must provide signs or signs on damaged roads to prevent traffic accidents. Factors that become obstacles to legal protection against the handling of victims due to traffic accidents are as follows: Human Factors, Vehicle Factors, Facilities and Infrastructure Factors, Weather, and Nature Factors. Keywords: Human Rights, Traffic Accidents, Perforated Roads